Generational Differences in Parity Progression in Australia: The Role of Sex Composition in Children - Gray, E; Evans, A; Kippen, R (My University, 2007)
This paper investigates generational differences in Australian parents’ desire for both a son and a daughter. We test the proposition that sex composition of existing children is an important factor in parental fertility decisions in low fertility societies, by comparing generations with different fertility regimes. In doing so, we explore whether the sex of children influences the propensity and timing of additional births. This paper uses data from the Household, Income and Labour Dynamics in Australia 2001 survey (N=5,327). We find evidence of a preference for a mixed-sex composition. Recent cohorts exhibit an additional mild preference for daughters. Further, we find that sex of existing children is least important for parents who had their children under a higher-fertility regime.
Australian Demographic and Social Research Institute Working Paper
Keywords: Families -- Fertility; Families; Families and relationships; Culture and language; Culture, identity and language; Families and relationships; Culture and identity